No impact of mineralocorticoid receptor antagonists on long‐term recurrences of ventricular tachyarrhythmias. Issue 2 (5th January 2021) - Schupp, Tobias; Akin, Ibrahim; Reiser, Linda; Bollow, Armin; Taton, Gabriel; Borggrefe, Martin; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Barre, Max; Müller, Julian; Weidner, Kathrin; et al.
Abstract: Objective: The study sought to assess the prognostic impact of treatment with mineralocorticoid receptor antagonists (MRA) on recurrences of ventricular tachyarrhythmias in implantable cardioverter‐defibrillator (ICD) recipients with systolic heart failure (HF). Background: Data regarding the outcome of patients with ventricular tachyarrhythmias treated with MRA is limited. Methods: A large retrospective registry was used including consecutive ICD recipients with systolic HF (i.e., left ventricular ejection fraction < 45%) and index episodes of ventricular tachyarrhythmias from 2002 to 2016. Patients treated with MRA were compared to patients without (non‐MRA). Kaplan–Meier and multivariable Cox regression analyses were applied for the evaluation of the primary endpoint defined as first recurrence of ventricular tachyarrhythmias at five years. Secondary endpoints were appropriate ICD therapies, first cardiac rehospitalization, and all‐cause mortality. Results: 366 ICD recipients with systolic HF were included, 20% treated with MRA (spironolactone: 65%; eplerenone: 35%) and 80% without. At five years, treatment with MRA was not associated with the primary endpoint of first recurrence of ventricular tachyarrhythmias [47% vs. 48%, log‐rank p  = 0.732; hazard ratio (HR) = 1.067; 95% confidence interval (CI) 0.736–1.546; p  = 0.732]. Accordingly, risk of first appropriate ICD therapies, first cardiac rehospitalization, and all‐cause mortality were not affected by the presence of MRA therapy. Finally, patients with spironolactone and eplerenone had comparable risk of first recurrences of ventricular tachyarrhythmias (50% vs. 45%; p  = 0.255; HR = 2.263; 95% CI 0.495–10.341; p  = 0.292). Conclusion: Treatment with MRA was not associated with recurrences of ventricular tachyarrhythmias and ICD therapies at five years.